Interlayer valley excitons in heterobilayers of transition metal dichalcogenides. Issue 11 (November 2018) - Rivera, Pasqual; Yu, Hongyi; Seyler, Kyle; Wilson, Nathan; Yao, Wang; Xu, Xiaodong
Abstract Stacking different two-dimensional crystals into van der Waals heterostructures provides an exciting approach to designing quantum materials that can harness and extend the already fascinating properties of the constituents. Heterobilayers of transition metal dichalcogenides are particularly attractive for low-dimensional semiconductor optics because they host interlayer excitons—with electrons and holes localized in different layers—which inherit valley-contrasting physics from the monolayers and thereby possess various novel and appealing properties compared to other solid-state nanostructures. This Review presents the contemporary experimental and theoretical understanding of these interlayer excitons. We discuss their unique optical properties arising from the underlying valley physics, the strong many-body interactions and electrical control resulting from the electric dipole moment, and the unique effects of a moiré superlattice on the interlayer exciton potential landscape and optical properties. This Review discusses the contemporary experimental and theoretical understanding of interlayer excitons in heterobilayers of transition metal dichalcogenides.